SOCIO-ECONOMIC DISPARITIES AND NATIONAL SECURITY OF PAKISTAN (Journal of Contemporary Studies, 2022)
Socio-economic disparities can pose threat to the security of a nation-state. They may even threaten a state’s survival. Thereby States have to adopt a comprehensive security approach to address socio-economic disparities. Pakistan is also challenged by socio-economic disparities caused by several internal and external factors. National Security Policy (NSP) 2022-2026 has duly recognised these factors and proposed a comprehensive security paradigm for the country. This study deploys a Comprehensive security approach as propounded by Copenhagen School to understand the linkage between socio-economic disparities and the national security of Pakistan. It attempts to explain how socio-economic disparities affect Pakistan's national security and what can be done to address them.